The reconstruction of the source base of military and topographical descriptions of Ukraine in the late 40th - early 50th of ХІХ century - Inna Petrova (Cхід, 2013)
The article is devoted to the problem of formation and development of system of military and topographical inspections in the Russian empire of ХІХc . Analyzing the problem of creation of military and topographical descriptions, the author first of all pays attention to the research of source base descriptively statistical sources, to establishment of level of their representativeness and reliability. Thanks to attraction of the historical and comparative method the author of article managed to reconstruct completely source base of military and statistical works, to establish the level of proficiency of the authors of descriptions by methods of source criticism. By the analysis of semantic loading of descriptions of the Volynsk, Kiev, Taurian and Chernigov provinces the author succeeded to show all list of documentary sources which were used by authors of descriptions at creation of their creation (legislative, descriptive and statistical, office work, sources of a personal origin, etc.) in the article. Investigating a problem of the source basis of military and topographical descriptions the author established that the majority of descriptions have a compilation basis. However, the compilation as a method of writing of military and topographical works was a natural stage of development of military and geographical thought of that period. As to investigate a significant amount of versatile questions without relying on scientific researches it was rather difficult. Only by attraction of a significant amount of sources it was possible to provide descriptions a complete substantial form. Similar research opens new opportunities for reconsideration of a problem of informational content of military and topographical descriptions of Ukraine in the late 40th - early 50th of XIX century.